Transformation of approaches to personnel’s motivation in the conditions of the newest managerial paradigm - Doronina, Olha (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The relevance of a research is caused by an important role of personnel’s motivation in the management system and need of ensuring its flexibility according to internal and to external changes. The article purpose is to study the conceptual bases of personnel’s motivation in the conditions of new economy and to suggest the directions of transformation of managerial approaches to personnel’s motivation. Design/methodology/approach. The realization of goals and objectives prompted the implementation of the following general scientific methods: the method of monographic and logical analysis, axiological and system approach, comparison. Theoretical and methodological basis of the research are works of domestic scientists, aimed at studying current problems of motivation and new economy’s development. Findings. Innovative labour is the dominating labour’s type in the conditions of new economy. In article features of innovative work which are determinants of transformation of approaches to personnel’s motivation are marked out. The essence of transformation of managerial approaches to personnel’s motivation in the conditions of new economy is determined. The visualized representation of the transformation directions of approaches to personnel’s motivation is offered. Researchlimitations/implications. The scientific value of a research consists in enrichment of modern science determination of essence of transformation of managerial approaches to personnel’s motivation in the conditions of new economy. There has been proved the directions of this transformation. There are change of requirements and values of employees, increase of a role of non-material motivation, application of new payment systems, strengthening of a self-motivation role, etc. Originality/value. Results of a research should become a basis of development of updated motivational systems and methods of motivation in the organizations which aim to provide achievement of its purposes through involvement of innovative employee, their development and motivation.